A Bibliography of Publications in Economic and Social History printed in Poland in 1977 - Kowal, Ewelina; Kowal, Stefan (Studia Historiae Oeconomicae, 1979)
A Bibliography of Publications in Economic and Social History in Poland in 1977 I. Bibliography 309 II. Methodology, thoory and history of oconomic thought 309 III. Sources and source studies 310 IV. General publications 311 V. Demography 314 VI. Social structure and mobility 317 VII. Labour, social movements and trade union 320 VIII. Social and economic relations in rural communities 322 IX. Towns and urbanization processes 324 X. Industry, mining, handicraft and architecture 327 XI. Transport and communication 331 XII. Maritime economy, aquatic economy 331 XIII. Trade 331 XIV. Credit, finance, money and prices 332 XV. Insurance and social welfare 334 XVI. Consumption 336